HLA-A SNPs and amino acid variants are associated with nasopharyngeal carcinoma in Malaysian Chinese - Chin, Yoon-Ming; Mushiroda, T.; Takahashi, A.; Kubo, M.; Krishnan, G.; Yap, Lee-Fah; Teo, Soo-Hwang; Lim, P.Vey-Hong; Yap, Yoke-Yeow; Pua, Kin-Choo; Kamatani, N.; Nakamura, Y.; et al. (John Wiley & Sons, 2015)
Nasopharyngeal carcinoma (NPC) arises from the mucosal epithelium of the nasopharynx and is constantly associated with Epstein-Barr virus type 1 (EBV-1) infection. We carried out a genome-wide association study (GWAS) of 575,247 autosomal SNPs in 184 NPC patients and 236 healthy controls of Malaysian Chinese ethnicity. Potential association signals were replicated in a separate cohort of 260 NPC patients and 245 healthy controls. We confirmed the association of HLA-A to NPC with the strongest signal detected in rs3869062 (p=1.73 x 10(-9)). HLA-A fine mapping revealed associations in the amino acid variants as well as its corresponding SNPs in the antigen peptide binding groove (p(HLA-A-aa-site-99)=3.79 x 10(-8), p(rs1136697)=3.79 x 10(-8)) and T-cell receptor binding site (p(HLA-A-aa-site-145)=1.41 x 10(-4), p(rs1059520)=1.41 x 10(-4)) of the HLA-A. We also detected strong association signals in the 5-UTR region with predicted active promoter states (p(rs41545520)=7.91 x 10(-8)). SNP rs41545520 is a potential binding site for repressor ATF3, with increased binding affinity for rs41545520-G correlated with reduced HLA-A expression. Multivariate logistic regression diminished the effects of HLA-A amino acid variants and SNPs, indicating a correlation with the effects of HLA-A*11:01, and to a lesser extent HLA-A*02:07. We report the strong genetic influence of HLA-A on NPC susceptibility in the Malaysian Chinese. What's new? Certain variants of the HLA-A gene are linked to either resistance or susceptibility in nasopharyngeal carcinoma (NPC). But which variants are most strongly associated with effects in NPC remains unclear. Here, high resolution fine-mapping of the HLA-A region was used to better understand the effects of variants on peptide loading or HLA-A expression in a Malaysian Chinese population. Variants showing potential epigenetic, peptide-loading function and T-cell immune response were correlated with the effects of HLA-A*11:01, a protective HLA-A allele. Most other HLA-A variants did not appear to possess any potential function.